2022
DOI: 10.21203/rs.3.rs-1843268/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship Between Stress Life Events and Adolescents' Sleep Problems: A Moderated Mediation Model

Abstract: In recent years, adolescent sleep problems have received increasing attention. Stressful life events have been found to be a risk factor for sleep problems, but little is known about the components that may explain or influence this association. To investigate this, present research tested whether depressive symptoms mediated the association between stressful life events and adolescents' sleep problems, as well as whether emotional regulation skills decreased this process. A sample of 513 Chinese university st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Xinyu Li etal. found that negative emotions such as anxiety or depression negatively affect sleep quality [7] . It has been shown that cell phone addiction significantly predicts anxiety [8] , while anxiety also significantly predicts cell phone addiction [9] , and the two may influence each other and be causal.…”
Section: Introductionmentioning
confidence: 99%
“…Xinyu Li etal. found that negative emotions such as anxiety or depression negatively affect sleep quality [7] . It has been shown that cell phone addiction significantly predicts anxiety [8] , while anxiety also significantly predicts cell phone addiction [9] , and the two may influence each other and be causal.…”
Section: Introductionmentioning
confidence: 99%